Integration of Thermo-Responsive Materials Applied to Bio-Inspired Structures - Elton Lima; Hilma Ferreira; Luís Mateus; Amilton Arruda (Biomimetics)
This paper investigates the integration of thermo-responsive materials into bio-inspired structures, combining biomimicry and adaptive technologies in architecture. A problem-based biomimetic approach and a morphological analogy with the plate-type snowflake—known for its lightness, transparency, and crystalline organisation—were adopted to develop the geometry of an architectural pavilion. This research highlights glass as a main constructive material, analysing the potential of thermochromic film and the hydrogel technique, both inserted in the context of thermo-responsiveness. In this regard, the focus is on adaptations to temperature changes, exploring how these materials can alter their properties in response to solar incidence, offering solutions for energy efficiency, thermal regulation, and environmental adaptation. The pavilion demonstrates that this integration is feasible, and this is supported by an interdisciplinary approach that combines materials science, bio-inspired design, and practical experimentation. It also highlights biomimicry’s fundamental role as a tool for guiding the development of innovative architectural geometries, while thermo-responsive materials expand the possibilities for creating structures that are adaptable to temperature variations and solar exposure. The conclusion points to the applicability and relevance of this combination, highlighting the transformative potential of thermo-responsive materials in architectural projects, especially in the development of lightweight, transparent, and environmentally responsive structures.